ANALISIS PELAKSANAAN PROGRAM IMUNISASI DPT- HB- HIB PENTAVALEN BOOSTER PADA BADUTA DI PUSKESMAS KOTA SEMARANG (Studi Kasus pada Puskesmas Halmahera) - Rahma, Fanny Pradila; Suryoputro, Antono; Fatmasari, Eka Yunila (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Diphtheria is one of the main causes of child mortality, where 40% occur in children under 5 years of age. The incidence of Diphtheria in Semarang City in 2017 amounted to 2 cases and KLB was one of them in the Halmahera Health Center. As an intervention, the baby is obliged to get basic DPT Immunization 3 times and pentavalent booster immunization up to 24 months of age. The purpose of this study is to describe the description through an analysis of the implementation of the DPT-HB-Hib Advanced Immunization program in Batita in the work area of the Halmahera Health Center. This type of research is qualitative with a descriptive analytic approach. Data collection was carried out by in-depth interviews and observations based on purposive sampling criteria. Subjects in the study were 3 implementing midwives, 1 KIA program coordinator, and a pharmacist as the main informant; Semarang health officer, toddler parents, gasurkes and cadres as triangulation informants. The variables studied are resources, funding, methods, infrastructure, planning, organizing, implementing, evaluating, and environment.The result of this study is the implementation of pentavalen immunisation in Halmahera Health Center was not optimum. The coverage of its program was only 32,8% from January until June 2017. Thus, there still about 49,7% infants had not been receiving booster immunization during January-June 2017 there. There also lacks including the knowledge of the midwives, Kader’s contributions towards the program, infants’ presence and the immunization program schedulling.